Peranan Pemerintah Desa Bulutellue dalam Memberdayakan Masyarakat di Era Otonomi Daerah - Abdul Rahman Rahman (Training & Research Institute - Jeramba Ilmu Sukses, 2023)
With the birth of Law No. 32 of 2004 on regional autonomy and Government Regulation No. 72 of 2005 on the village provides an opportunity to villagers to control and manage his own household, with the requirements mandated by the village government held to the principles of democracy, the role of and the community, equality, justice, and considering the potential and diversity of the region. The community has a central enough role to determine policy options that suit the needs and aspirations. But in reality, the village government has not been very instrumental in empowering potential contained in its citizens. Therefore in this study will be examined how the government's efforts in empowering rural communities. The purpose of this study was to determine and analyze the role of government in the village community as well as reviewing empowering driving and inhibiting factors in empowering people in the Bulutellue Village, Bulupoddo District of Sinjai Regency. Result this study is expected to benefit both theoretically and in practice both for the residents in Bulutellue Village, Ponre District of Sinjai Regency in particular and society in general. Result This study is classified as a descriptive qualitative research. With this approach the researcher to explore the nature of information about government's role in the rural village. The main data sources are the words and actions of key respondents sampled in this study. Techniques in exploring the data is through observation, interviews, and research dokumentation. Result of three main elements which include community development, community service and community development in the Bulutellue Village shows that the government has managed to build communication so that people can actively participate in the empowerment of the village, although recognized by the government of the village that there are factors that inhibit and promote community empowerment efforts.